Living arrangement pattern nursing home occupants based activities and behavior - Evian Devi (ARTEKS : Jurnal Teknik Arsitektur, 2016)
Physical comfort in a building can give an effect to the psychological inhabitans. In the design of nursing homes, where the residents are elderly, certainly they have a different physical comfort with a younger people. The degenerative disease on elderly cause the need for special attention in architecture, especially on safety and comfort. Currently the nursing homes, mostly do not noticed it well, so still discovered lots of the elderlies got an accident and depressed in a nursing home. This research purpose to know the relationship between the aspects of both comfort and safety for elderly in nursing home that can make the elderly feel comfortable and happy living in their residence. The methods of this research are as follows: first, understand the criteria of elderly in related literatures and observations regarding to the elderly and other related literatures that subscribe with safety and comfort. Second, the literatures study was used to analyze the case study such as Nursing Home Wisma Mulia (Jakarta), Nursing Home Senjarawi (Bandung), and Nursing Home Muara Kasih (Bogor). The results of analysis from the case studies based on the literature, produce an architectural design criterion for the review occupancy elderly. The results of this research concluded that the design of the comfortable and safe against risk of any accident that may occur to the elderly, provided a circulation which can be passes by two wheelchairs at once and freeway, provided handrail in the circulation, provided ramp in any difference level of floor, and using a contrast color but dominant in light and warm color. The other considerations are the availability nostalgic room, playroom for children and the other facility that make the frequency of their families, visiting more often.